Solar Cell-Powered UAVs for Marathon Flights as a Geographic Data Retrieval Tool - Fadila, Juniardi Nur; Basid, Puspa Miladin Nuraida Safitri A. (2019 International Conference on Electrical Engineering and Computer Science (ICECOS), 2019)
From year to year, the need for geographic information data as research subjects is increasing, as well as the need for more efficient survey tools. Not only for research and survey but also for disaster mitigation and urban planning even for film. One way to acquire geographic data is to use an Unmanned Aerial Vehicle (UAV). With UAVs we can acquire geographic maps quickly without having to drive around the site. UAV is currently one of the global technologies but, UAVs have several disadvantages where one of them is the length of flight time which is very dependent on the electrical energy of the battery, while the site used for research sometimes reaches hundreds of hectares. In this study, we will discuss the case and try to solve the problem by using solar cells to provide longer flight times for UAVs. This research will help land surveyors to improve the quality of their performance.